A retrospective comparative study of feto-maternal outcome in first and second stage caesarean section - Jain, Nidhi; Lal, Prabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The incidence of caesarean section has increased tremendously over the recent years. The most common indications of caesarean section are fetal distress and previous caesarean section during first stage caesarean section and cephalo-pelvic disproportion and fetal distress during second stage caesarean section. The objective of this study was to compare maternal and fetal outcomes between first and second stage caesarean section. Methods: A retrospective cohort study was carried out in the department of obstetrics and gynaecology at a tertiary hospital over a period of 6 months. Comparison was done between two groups, women who underwent caesarean section during first stage (group I) and during second stage (group II). Data was collected and compared on basis of maternal and fetal outcomes. Results: Among maternal complications, PPH occurred in significantly higher number of women in group II (21%) than in group I (9%). 21% of women in group II required blood transfusion and 7% admitted to ICU. Bladder injury and uterine incision extension was seen in more number of cases in group II (6% and 7% respectively), difference being statistically insignificant. Neonatal complications were significantly higher in group II. Conclusions: Second stage caesarean sections are associated with significant maternal and fetal morbidities, thus necessitating presence of senior obstetrician at time of decision and conductance of procedure.